(untitled) (Journal of Informatics Education and Research, 2026)
Regardless of the digital advancements offered by CARA through CARINGS, there is still an average delay of 2-4 years to complete an adoption process in India that is governed by the JJ Act, 2015 and the Adoption Regulations, 2022. This study critically evaluates CARA’s 2026 OM directives regarding their procedures (particularly for LFA adoptions), their requirements for proper documentation, and their provisions to protect the privacy of all children who are placed with families [rather than having any agency involved in placing children and/or procedural issues]. While it has been proven that using digital tools has speeded up the matching process of children with families, delays in the process of inquiry/tracing have not been reduced by using these tools, thus indicating that the entire lifecycle of the adoption process must be managed within a comprehensive timeline in order to ensure accountability to all parties involved.